The Effect Of Cash Ratio (CR) And Debt To Equity Ratio (DER) On Return On Equity (ROE) At Pt Ace Hardware Tbk 2012-2024 - Fadli , Achmad Agus Yasin; Purwantina , Finka (Journal of Management, Economic, and Accounting, 2025)
This study aims to analyze the effect of Cash Ratio (CR) and Debt to Equity Ratio (DER) on Return on Equity (ROE) at PT Ace Hardware Tbk during the period 2012–2024. The method used is a quantitative approach. The data used are secondary data in the form of the company's annual financial reports, and are processed using SPSS. The results of the partial test (t test) show that Cash Ratio (CR) has an effect on Return On Equity (ROE) (t count -7.033; sig. 0.001), while Debt to Equity Ratio has no effect (t count -1.434; sig. 0.182). The simultaneous test (F test) shows that Cash Ratio (CR) and Debt to equity ratio (DER) together have an effect on Return On Equity (ROE), with a calculated F value of 27.596 and a significance of 0.01. This study indicates that liquidity, as measured by the Cash Ratio (CR), plays a significant role in improving a company's financial performance, while capital structure, as measured by the Debt to Equity Ratio (DER), shows no effect. Therefore, liquidity management is a crucial factor in efforts to improve Return on Equity (ROE) at PT Ace Hardware Tbk.